The Use of a Vision System for Monitoring Chick Embryos in Incubator - Al-Ansi, Abdullah; Ryabtsev , V; Utkina , T (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2023)
Background: Determine the quality of hatching eggs and control the process of their embryonic development, it is necessary to perform candling of eggs, which makes it possible to identify and eliminate the causes of low hatching of chicks. Contribution: The proposed vision system for processing images of chicken eggs makes it possible to distinguish fertilized eggs from unfertilized ones, which makes it possible to change the parameters of the incubator in the event of a large number of dead embryos. Method: With the help of the National Instruments Vision Assistant module, which simplifies the collection, reproduction and storage of images recorded using a video camera connected via a FireWire interface, an incubator vision system has been developed. Results: The yield of healthy chicks is increased due to the periodic automatic candling of eggs and the timely regulation of parameters during the incubation process. Conclusion: Being able to monitor embryo development more closely allows you to determine the optimal time to change incubation parameters, such as humidity, to create the best conditions for egg hatching, leading to more efficient chick production. Similarly, the ability to use different light and temperature conditions to influence chick hatch time can allow for a faster incubation process and hatch healthy chicks in a shorter period of time.